2021
DOI: 10.1002/cbm.2215
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and risks of conjugal visits in prison: A systematic literature review

Abstract: Background Imprisonment impacts on lives beyond the prisoner's. In particular, family and intimate relationships are affected. Only some countries permit private conjugal visits in prison between a prisoner and community living partner. Aims Our aim was to find evidence from published international literature on the safety, benefits or harms of such visits. Methods A systematic literature review was conducted using broad search terms, including words like ‘private’ and ‘family’, to maximise search sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…(2005, p. 331) reported that in‐person visits were more critical for relationships with children and partners than other forms of contact. This work is built on earlier work by Carlson and Cervera (1991) (also see Hensley et al., 2000; Vladu et al., 2021) who found that conjugal visits played an important role in maintaining family ties and intimate marital relationships during imprisonment. (A conjugal visit is a specific type of visit in which prisoners may engage in sexual intercourse with their partners).…”
Section: Introductionmentioning
confidence: 88%
“…(2005, p. 331) reported that in‐person visits were more critical for relationships with children and partners than other forms of contact. This work is built on earlier work by Carlson and Cervera (1991) (also see Hensley et al., 2000; Vladu et al., 2021) who found that conjugal visits played an important role in maintaining family ties and intimate marital relationships during imprisonment. (A conjugal visit is a specific type of visit in which prisoners may engage in sexual intercourse with their partners).…”
Section: Introductionmentioning
confidence: 88%